2010
DOI: 10.1074/jbc.m109.034421
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Shuttling and Mitochondrial Function of Thioredoxin-interacting Protein

Abstract: The thioredoxin-interacting protein TXNIP is a ubiquitously expressed redox protein that promotes apoptosis. Recently, we found that TXNIP deficiency protects against type 1 and 2 diabetes by inhibiting beta cell apoptosis and maintaining pancreatic beta cell mass, indicating that TXNIP plays a key role in beta cell biology. However, very little is known about the intracellular localization and function of TXNIP, and although TXNIP has been thought to be a cytoplasmic protein, our immunohistochemistry studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
220
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(234 citation statements)
references
References 44 publications
12
220
1
1
Order By: Relevance
“…However, a significant portion (410%) of endogenous Redd1 is localized to the mitochondria, which regulates reactive oxygen species (ROS) (Horak et al, 2010). TXNIP is present in both the cytoplasm (Junn et al, 2000;Schulze et al, 2002Schulze et al, , 2004 and nucleus (Nishinaka et al, 2004;Saxena et al, 2010). TXNIP has also been reported to be present in mitochondria and has been shown to bind the mitochondrially localized TRX (Oka et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant portion (410%) of endogenous Redd1 is localized to the mitochondria, which regulates reactive oxygen species (ROS) (Horak et al, 2010). TXNIP is present in both the cytoplasm (Junn et al, 2000;Schulze et al, 2002Schulze et al, , 2004 and nucleus (Nishinaka et al, 2004;Saxena et al, 2010). TXNIP has also been reported to be present in mitochondria and has been shown to bind the mitochondrially localized TRX (Oka et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…TXNIP binds reduced Trx and prevents it from reducing Prx, thereby blocking cyclic Trx redox reactions. TXNIP has been implicated in the development of type 2 diabetes through several mechanisms, including promoting ␤-cell apoptosis by regulating Trx2 and ASK1 in the mitochondria (Saxena et al, 2010), inhibiting glucose uptake in fat tissue and skeletal muscle to increase insulin resistance (Parikh et al, 2007), stimulating glucose production in the liver (Chutkow et al, 2008), and regulating adipogenesis (Chutkow et al, 2010) and fatty acid utilization (Oka et al, 2006). TXNIP promotes oxidative damage in vascular endothelia to cause vascular pathology (Schulze et al, 2004) and regulates Schwann cell reactions in peripheral nerve repair through a receptor for the advanced glycation end products-TXNIP axis to induce peripheral nerve injury (Sbai et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] Under HG conditions, TxNIP has been implicated in impairing ROS scavenging by binding to and attenuating the antioxidant action of thioredoxin, a ubiquitous oxidoreductase. 14 In addition, we recently reported that TxNIP enhances HG-induced mitochondria-derived O 2 2 (superoxide) as well as cellular ROS, at least in part, by augmenting the mitochondrial and cytosolic NADPH oxidase isoform, Nox4, in cultured mesangial cells. 15 Thus, by increasing the generation and decreasing the degradation of ROS, HG-induced TxNIP may contribute to glucotoxicity, as observed by others and our group in pancreatic b cells.…”
mentioning
confidence: 99%